2017
DOI: 10.1186/s13068-016-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

When substrate inhibits and inhibitor activates: implications of β-glucosidases

Abstract: Backgroundβ-glucosidases (BGs) catalyze the hydrolysis of β-glycosidic bonds in glucose derivatives. They constitute an important group of enzymes with biotechnological interest like supporting cellulases in degradation of lignocellulose to fermentable sugars. In the latter context, the glucose tolerant BGs are of particular interest. These BGs often show peculiar kinetics, including inhibitory effects of substrates and activating effects of inhibitors, such as glucose or xylose. The mechanisms behind the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…4a we can observe that when glucose concentration is increased, β-glucosidases activities decreased, indicating that enzymes are inhibited by the product. In the enzymatic hydrolysis of lignocellulose biomass to fermentable sugars, an inevitable consequence is the accumulation of hydrolysis products at high concentrations, which may result in cellulases inhibition (Kuusk and Väljamäe, 2017), as observed in this study for β-glucosidases from the two selected fungi. According to (Guimarães et al, 2006), glucose inhibition is commonly cited in studies regarding microbial β-glucosidases.…”
Section: Glucose and Ethanol Effects On β-Glucosidases Activitiesmentioning
confidence: 64%
“…4a we can observe that when glucose concentration is increased, β-glucosidases activities decreased, indicating that enzymes are inhibited by the product. In the enzymatic hydrolysis of lignocellulose biomass to fermentable sugars, an inevitable consequence is the accumulation of hydrolysis products at high concentrations, which may result in cellulases inhibition (Kuusk and Väljamäe, 2017), as observed in this study for β-glucosidases from the two selected fungi. According to (Guimarães et al, 2006), glucose inhibition is commonly cited in studies regarding microbial β-glucosidases.…”
Section: Glucose and Ethanol Effects On β-Glucosidases Activitiesmentioning
confidence: 64%
“…The topology of the active site has also been associated with the tolerance of some enzymes to high concentration of glucose [ 28 , 29 , 35 ]. Furthermore, a recent theoretical study raised the possibility that competition of inhibitors with the non-productive binding of substrate may be a possible mechanism of glucose/xylose stimulation of β-glucosidases that have more than one glycosyl residue binding subsite in the aglycone binding site [ 36 ]. It has been recently proposed that the relative binding affinity/preference by sites at the entrance and middle of the substrate channel regulate the effects of glucose [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The B8CYA8 crystal structure in the presence of glucose and STD-NMR studies, however, show the interaction with glucose near the bottom of the active site pocket. Glucose inhibition has been attributed to binding to other allosteric sites, and by non-productive binding to other sites in the active site pocket [11, 45] However cooperativity in B8CYA8 could not be established by measurement of hill coefficient (Supplementary file, Table S6) which were around one in the wild-type and the mutants. The binding of glucose to secondary binding site(s) is, however, yet to be experimentally proven.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was reported that the addition of small amounts of glucose could reduce the non-productive binding of substrate to +1 and +2 subsites and stimulate enzyme activity [45]. A comparison with PDB structure 3F5K and 2O9P indicates the presence of the +2 subsite in B8CYA8 which can potentially assist in the non-productive binding of the substrate.…”
Section: Discussionmentioning
confidence: 99%